Dampak Pendidikan Gender terhadap Kesetaraan Jenis Kelamin di Pondok Pesantren Tahfidz Al-Quran Baytul Mukarromah Kabupaten Bone Sulawesi Selatan - Fentyrina, Andi (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The issue of gender equality in Islamic education, particularly within the context of Islamic boarding schools (pondok pesantren), remains a relevant topic for empirical study. Pondok pesantren, as religious educational institutions, not only play a role in the transmission of Islamic knowledge but also in shaping social relations and interaction patterns between male and female students (santri). This study aims to analyze gender education practices and their implications for gender equality at the Pondok Pesantren Tahfidz Al-Quran Baytul Mukarromah in Bone Regency, South Sulawesi. This research uses a qualitative approach with a descriptive-analytical research type. Data was collected through observation, in-depth interviews, and documentation studies involving administrators, male and female students, and teachers (ustaz/ustazah). Data analysis was conducted using the gender analysis framework of Access, Participation, Control, and Benefit (APKB) to gain a deeper understanding of gender education relations and gender equality in the practices of pesantren education. Preliminary findings show active participation of female students in both academic and non-academic activities, including leadership and achievements, indicating the openness of equal opportunities in certain aspects. However, this study begins with the assumption that this equality may not be substantive and still requires further analysis of aspects such as control and the distribution of educational benefits. It is hoped that this study can contribute empirically to the development of gender perspective in Islamic education studies and serve as a practical reference for the development of a more equitable and gender-responsive tahfidz pesantren education model.